Propuesta de un plan estratégico para la finca agrícola "Seis hermanos" en el Cantón Buena Fe. - Guanoluisa Toapanta, Fanny Magdalena (2015)
This research was conducted at the farm "Six Brothers" Canton Good Faith, Los Rios Province. This research was developed through interviews and direct surveys of the owner and workers that helped to determine the current status of the farm. According to the results of research it conducted it was concluded that the farm lacked a strategic plan, which prevented this from developing properly. Regarding strategies were designed for each department of the farm especially for administrative and production area, then the design of structural organization was held, this is what made vertically, considering the organizational size of the estate, in which clearly distinguishes the hierarchical level. Once the structural organization designed manual functions for each of the departments, focusing on the activities performed by employees of the same was prepared. Its directional basis as mission and vision were also determined, to help you see where you are going. Conclusions and recommendations, which were obtained after having performed the research analysis is then carried out.